Optimization of small agarwood hydrodistillation systems: An analytical study to determine the required cooling water flow for optimal operation of an agarwood-hydrodistillation system - T., Mueller; S. A., Che Ghani; W. S., Wan Harun; A. H., Abdullah (2017)
Cooling systems in a hydrodistillation consists of clevenger type condenser that condensates steam for collecting extracted essential oil. An analytical study was used to compute the required cooling water flow in the condenser to completely change the generated steam from the still to liquid in the heat exchanger. In the simplified model of the counter flow heat exchanger configuration, the Gnielinski correlation was used to calculate the heat transfer coefficient. For variation of the boiler heat flows the corresponding required mass flow rate for optimal operation can be determined from this analytical study. The analyses has shown, that for the given system, a massflow of more than 2000 kg/h is needed to operate at a capacity of 5 kW. Further optimization is needed to operate under reasonable conditions. The results can later be used for optimising the design parameters of the hydrodistillation to extract essential oil at high productivity. Engineering knowledge and fundamentals have to be transferred to the planner and operators to optimize the thermal and hydraulic design of hydro distillation plants, especially in rural areas.